â€œBREAD & ROSESâ€: SOCIOLOGICAL ANALYSIS OF LITERATURE AND ITS RELEVANCE TO THE PRESENT IN THE CONTEXT OF THE WORKING CLASS - Faza Fauziyyah (Saksama: Jurnal Sastra, 2023)
The article "Bread & Roses": An Analysis of the Sociology of Literature and Its Relevance to the Present in the Context of the Working Class" was created with the intention of explaining how working class people express their grievances in the form of literary works, called working class literature. Working class literature refers to a type of literature or literary work that raises issues, experiences, and realities of working class or working class life in society. Working class literature often describes the lives, struggles, and challenges faced by social groups working in industry, factories, agriculture, or other occupational sectors associated with manual or labor work. This article aims to deepen the understanding of how the working class expresses their grievances and protests through literary works, especially in the context of working class literature. Working class literature refers to a type of literature that specifically raises the issues, experiences, and realities of working class or working class life in society. The focus is often on the daily lives, challenges, and struggles faced by social groups working in industry, factories, agriculture, and manual labor or other labor. In this article, research is conducted by analyzing the text of the poem "Bread &; Roses" by Hakim Bellamy as a relevant example. The analysis is complemented by searching data through journals, websites, and books to support findings and broader understanding. Through an analysis of the content of this poem, we can gain insight into how workers convey their grievances and grievances through literary form, as well as their relevance to the situation and conditions of the working class today. In this study, data were obtained through textual analysis methods and search for diverse sources of information, as well as using a literary sociology approach, namely by paying attention to social phenomena that occur both when in the time setting in the poem (1787), when the poem was written (2011) and what its relevance is to the present (2023). The theory relevant to this research according to the author is the theory of Marxism, regarding the working class. By deepening the understanding of working-class literature and seeing concretization in the poem "Bread &; Roses", this article contributes to broadening the horizons of the way working class grievances and protests are expressed through literary form. The results of this study can provide a deeper understanding of the relevance of poetry to today's social and economic context, especially in relation to the struggles and aspirations of the working class. By analyzing the content of Hakim Bellamy's poem "Bread &; Roses", we can find out how the protests and grievances of workers are channeled into literary works and what their relevance is to the present.